KONTRIBUSI ULAMA HADIS DALAM PENGEMBANGAN ILMU HADIS: SEBUAH TINJAUAN HISTORIS DAN LITERATUR - Tamjidnor Tamjidnor (Adisam Publisher, 2025)
This study examines the contribution of hadith scholars in the development of hadith science through a historical perspective and literature review. The main focus of the study is to analyze the evolution of hadith science from the early days of Islam to the contemporary era and to identify the key roles of the scholars in this process. The literature review method was used in this study. The results show that the contribution of hadith scholars was significant in several aspects: (1) the collection and codification of hadith, (2) the development of hadith criticism methodology, (3) the establishment of hadith classification systems, and (4) the writing of monumental works in hadith science. The study also reveals that the development of hadith science was not limited to the classical era but continues to the present with adaptations to contemporary challenges and opportunities. Thus, the conclusion emphasizes the importance of the contribution of hadith scholars in maintaining the authenticity and relevance of hadith science. It also underscores the need for further studies on the integration of classical methods with modern approaches in hadith science and its implications for the understanding and application of hadith in the contemporary context.